Disability pension among persons with chronic illness: Differential impact of a Danish policy reform. (30th September 2020) - Mathisen, J; Jensen, N K; Bjorner, J B; Brønnum-Hansen, H; Christensen, U; Thielen, K; Gadeberg, A K; Andersen, I
Abstract: Background: Denmark implemented a reform in 2013 that tightened the disability pension criteria and expanded a subsidized job scheme. Before the reform, disability pensions were most often granted because of chronic disease and more often to persons with low job qualifications. However, no evaluation has assessed whether the effects of the reform differ according to social class. This register-based, nation-wide cohort study investigates potential differential impact of the reform according to labor market affiliation. Methods: A pre-post study design was used to compare the probability of being granted disability pension or flexi-jobs five years after vs. five years before the reform. Data were available from 480, 809 persons between 40 and 65 years of age who suffered from at least one of six types of chronic disease. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated. Results: The probability of being granted disability pension was halved after the reform (HR = 0.49, CI: 0.47 - 0.50). The impact was strongest for persons previously receiving cash benefits (HR = 0.38, CI: 0.33-0.43) or sickness absence benefits (HR = 0.31, CI: 0.24 - 0.39). Also, the impact was stronger for persons working in manual jobs than for persons working in non-manual jobs. The probability of being granted flexi-job decreased by one fourth (HR = 0.76, CI: 0.74 - 0.79). Conclusions: After the reform, it was less likely for persons with chronic illness to be awarded disability pension or subsidized job-schemes. The impact on disability pensions was largest among those who were already outside the labor market or work in manual jobs. Key messages: The rates of disability pensions and subsidized job-schemes decreased after the reform. The impact was larger for persons outside the labor market and for those working in manual jobs.